Two-phase sequential solid-state fermentation based on a synthetic microbial community enhances short-chain fatty acid production from sugarcane dry leaves - Caixiang Wei; Zeming Bu; Qi Yan; Xiaohua Huang; Xinghua Cai; Caixia Zou (Innovative Food Science & Emerging Technologies, 2026)

Functional differences between healthy and stressed soils: Rare and abundant root exudates as a regulatory switch for quorum sensing in rhizosphere microbiota - Yueyi Liu; Zhenchao Wu; Zeming Ye; Liangyang Mao; Xiujun Tu; Yuhao Guo; Weige Yao; Ying Yang; Shuo Li; Jie Kang; Baiyan Cai; Jingping Ge (Plant and Soil, 2026)

Microplastics inhibit oxytetracycline degradation in soils: Insights into biofilm-enhanced adsorption and microbial community shifts - Ting Guo; Zeming Zhang; Ben Yu; Yimin Cai; Da Ouyang; Williamson Gustave; Haibo Zhang (Journal of Hazardous Materials, 2026)

Identification of Mitochondrial and Succinylation Modification-Related Gene Signature in Ischemic Stroke - Lixia Wang; Jishuai Zhao; Hui Cai; Xiaoling Ying; Yonglei Liu; Zeming Luo; Heyan Chen; Lin Yang (Molecular Neurobiology, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

Mangrove plants are promising bioindicator of coastal atmospheric microplastics pollution - Yuanyin Huang; Ziying Zhu; Tianmu Li; Minqian Li; Zeming Cai; Xiaocui Wang; Han Gong; Muting Yan (Journal of Hazardous Materials, 2024)

Combined effects of microplastics and antibiotic-resistant bacteria on Daphnia magna growth and expression of functional genes - Xiaofeng Chen; Xiaocui Wang; Yuanyin Huang; Ziying Zhu; Tianmu Li; Zeming Cai; Minqian Li; Han Gong; Muting Yan (Science of The Total Environment, 2023)

Characterization of modified rice straw biochar in immobilizing Bacillus subtilis 168 and evaluation on its role as a novel agent for zearalenone-removal delivery - Jie Han; Jiao Zhang; Jun Meng; Yuanqi Cai; Mo Cheng; Siyu Wu; Zeming Li (Journal of Hazardous Materials, 2023)

Microplastic pollution and enrichment of distinct microbiota in sediment of mangrove in Zhujiang River estuary, China - Muting Yan; Xiaofeng Chen; Wei Chu; Weixin Li; Minqian Li; Zeming Cai; Han Gong (Journal of Oceanology and Limnology, 2023)